Analysis of Focal Mechanisms Using Waveform Inversion; Case Study of Pidie Jaya Earthquake December 7, 2016 - Qadariyah Qadariah; Andrean VH Simanjuntak; Muksin Umar (PSI-Aceh, 2018)
Salah satu gempa bumi yang berdampak pada kerusakan rumah penduduk telah terjadi di Sumatra tepatnya adalah daerah Pidie Jaya pada tanggal 7 Desember 2016, sebesar Mw 6.5. Pada penelitian ini akan dilakukan analisa pada mekanisme fokal gempa bumi menggunakan inversi wavefom dari seismogram digital tiga komponen. Mekanisme fokal gempa bumi dimodelkan dari proses inversi tensor momen menggunakan program ISOLA. Hasil inversi tensor momen menunjukan bahwa gempa bumi Pidie Jaya merupakan gempa bumi dengan mekanisme sesar geser dengan bidang nodal 1; strike 254°, dip 80°, slip 48° dan bidang nodal 2; strike 153°, dip 42°, slip 165°.One of destructive earthquake that occurred in Sumatra region is Pidie Jaya earthquake, on the 7th of December, 2016 with Mw 6,5. The aim of this study is to analyze the focal mechanism using waveform inversion three component digital seismogram. Earthquake focal mechanism is determined by moment tensor inversion method using ISOLA program. Moment tensor inversion results show that the solution of the focal mechanism of the Pidie Jaya earthquake is a strike-slip fault with nodal plane 1; strike 254°, dip 80°, slip 48° and nodal plane 2; strike 153°, dip 42°, slip 165°.Keywords: waveform inversion, earthquake, focal mechanism, strike-slip, Pidie Jaya